“Nature in Space” as Interior Concept for Resort Hotel in West Bandung - Andi Ade Fitri; Rizka Rachmawati; Vika Haristianti (Departement of Architecture, Universitas Islam Indonesia, 2020)
West Bandung has the potential and high appeal for the field of nature tourism. Beautiful scenery, fresh air, an arena of adventure, and cultural richness are the potentials of West Bandung Regency in developing tourism as a leading sector. As an area close to various tourist attractions, West Bandung can be an alternative location for tourists to stay and do recreational activities. From this phenomenon, temporary lodging facilities, such as resort hotels, are needed as a place to enjoy free time from hectic daily activities that target family tourists. The highest motive category for tourists coming to West Bandung is Physical/ Psychological Motivation, physical and mental motivation related to health, comfort, and relaxation. The result of literature studies shows that including natural elements, either directly or indirectly, in the immediate environment will be very influential in reducing blood pressure, lowering heart rate, increase productivity, and self-comfort. Based on the biophilic theory, improving relations with nature is important for healthy human development, including humans who use a space. To meet the motivational needs of its users, interaction with nature is a solution to be applied. The interior of the Resort Hotel in West Bandung applies the concept of “Nature in Space.” The concept applied is one of the important principles of biophilic design by applying natural materials, colors, and lighting. This study aimed to determine the type of interior space required to improve the user's physical and psychological health. The qualitative method was used in this study by collecting literature and questionnaires to 66 respondents from various backgrounds. This study's results are expected to provide knowledge related to the application concept of nature in the interior resort hotel as a place to stay and a means of relaxation to support its users' health and comfort.Keywords: Interior; Nature; Relaxation; Resort Hotel